2013
DOI: 10.1002/mc.22033
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB2 down‐regulation contributes to chemoresistance in head and neck cancer

Abstract: Resistance to cisplatin-based chemotherapy is responsible for the majority of deaths from head and neck squamous cell carcinoma (HNSCC). In this study, using genome-wide gene expression analysis to investigate potential molecular mediators of HNSCC chemoresistance, we identified SERPINB2, a known inhibitor of extracellular serine proteinase urokinase-type plasminogen activator (uPA), as an important candidate. Whereas SERPINB2 is known to function as a suppressor of uPA molecular cascades, many of which play i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Similarly, cytokines including IL‐1b , IL‐6 and IL‐8 are implicated in tumorigenesis and their increased expression is associated with the development, progression and therapeutic resistance in pancreatic cancer . The role of SERPINB2 , which encodes the plasminogen activator inhibitor 2, is context‐dependent in cancer and both tumor‐suppressing and promoting functions are reported . However, a potential tumor‐suppressive role of SERPINB2 is earlier described in pancreatic cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cytokines including IL‐1b , IL‐6 and IL‐8 are implicated in tumorigenesis and their increased expression is associated with the development, progression and therapeutic resistance in pancreatic cancer . The role of SERPINB2 , which encodes the plasminogen activator inhibitor 2, is context‐dependent in cancer and both tumor‐suppressing and promoting functions are reported . However, a potential tumor‐suppressive role of SERPINB2 is earlier described in pancreatic cancer .…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35] The role of SERPINB2, which encodes the plasminogen activator inhibitor 2, is contextdependent in cancer and both tumor-suppressing and promoting functions are reported. 36,37 However, a potential tumorsuppressive role of SERPINB2 is earlier described in pancreatic cancer. 38 Therefore, the significance of SERPINB2 in the context of NO • /Kynurenine/AHR mediated signaling in pancreatic cancer needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, clinical results reveal that a lower level of SERPINB2 expression is associated with poor prognosis and outcome in head and neck, gastric, breast, and lung cancers (53)(54)(55). In contrast, overexpression of SERPINB2 was found to result in suppression of invasion of cancer cells (56,57).…”
Section: Log2 Intensitymentioning
confidence: 98%
“…In contrast, decreased SerpinB2 levels have been correlated with unfavourable outcomes in breast18, head and neck19, gastric20 and liver21 cancers. Moreover, a recent study reported that the down-regulation of SerpinB2 is associated with an acquired resistance to cisplatin in head and neck squamous cell cancer22.…”
mentioning
confidence: 99%